LITERATURE REVIEW: PENGARUH ECCENTRIC EXERCISE TERHADAP PENINGKATAN KEKUATAN OTOT QUADRICEPS PADA CEDERA ANTERIOR CRUCIATE LIGAMENT (ACL): Literature Review: The Effect of Eccentric Exercise on Increasing Quadriceps Muscle Strength in Anterior Cruciate Ligament (ACL) Injuries - Afrizal Fauziansyah; M. Furqon Hidayatullah; Siswandari; Slamet Riyadi (ASSYIFA : Jurnal Ilmu Kesehatan, 2024)
Eccentric training is thought to increase quadriceps muscle strength, but there has been no systematic review analyzing the effect of eccentric training on increasing quadriceps muscle strength in ACL injuries. The aim of this study was to determine the effectiveness of eccentric training compared to other interventions in increasing quadriceps muscle strength in ACL injuries. The research method used this time was a literature review in accordance with the PRISMA 2020 guidelines. A systematic search was carried out using the Scopus, Science Direct and MDPI databases. The research results show consistent evidence that 6 out of 10 research articles show that eccentric training is effective in increasing quadriceps muscle strength in ACL injuries compared to other interventions; 1 in 10 articles showed that eccentric training was effective in increasing quadriceps muscle strength without similar intervention; 3 out of 10 articles explained that eccentric training significantly increased quadriceps muscle strength, but there was no significant difference with other interventions. This study supports the hypothesis that eccentric training is an effective method for increasing quadriceps muscle strength in ACL injuries compared to other interventions. Further research is needed to compare the most effective eccentric training protocols in increasing quadriceps muscle strength and the long-term effects that occur from their use.